2019
DOI: 10.9755/ejfa.2019.v31.i5.1954
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Application Increases Accumulation of Phenol substances in Kiwifruit during Storage

Abstract: To investigate the effect of melatonin on the fruit quality during storage, fruits of ‘Jingshi No 1’, a new yellow-fleshed kiwifruit variety, were used as materials by soaking in 0.1 mmol·L-1 melatonin (MT) solution. The results showed that MT treatment significantly delayed the decline of fruit hardness, reduced the loss of soluble protein, and significantly lowered the accumulation of malondialdehyde when compared with the control. Moreover, MT application improved content of antioxandants, such as total phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Furthermore, Zheng et al (2019) found that melatonin could maintain the nutritional and commercial value of fresh-cut pear fruit by inhibiting the expression of enzymatic browning-related genes but enhancing antioxidant capacity. Melatonin application could also increase accumulation of phenol substances in kiwifruit during storage (Wang et al, 2019b). Further results showed that the melatonin (0.1 and 1 mM) treatment could not only effectively improve the storage quality but also prolong shelf life of strawberry (Liu et al, 2018a).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, Zheng et al (2019) found that melatonin could maintain the nutritional and commercial value of fresh-cut pear fruit by inhibiting the expression of enzymatic browning-related genes but enhancing antioxidant capacity. Melatonin application could also increase accumulation of phenol substances in kiwifruit during storage (Wang et al, 2019b). Further results showed that the melatonin (0.1 and 1 mM) treatment could not only effectively improve the storage quality but also prolong shelf life of strawberry (Liu et al, 2018a).…”
Section: Introductionmentioning
confidence: 91%
“…PAL activity increased in cherry tomatoes due to melatonin application; this response positively impacted fruit phenolic and flavonoid total and lignin content during storage [99]. In addition, changes in metabolite content have also increased in several other fruits that have been studied, such as plums [77], mangoes [19,84], and kiwis [83].…”
Section: Solanum Lycopersicum 50mentioning
confidence: 98%